A Vietnamese-English cross-cultural study of expressing sarcasm - Nguyễn, Thùy Linh (ĐHNN, 2017)
The availability of sarcasm is a matter-of-fact which has been going without much awareness even of the user. Moreover, the use of puns in expressing sarcasm, in spite of being very interesting and noteworthy, has received hardly any extensive research. Pu (...)